AI on Learning English: Application, Benefit, and Threat - Enik Rukiati; Julien Arief Wicaksono; Gullit Tornado Taufan; Degita Danur Suharsono (P3M Politeknik Negeri Jember, 2023)
The use of artificial intelligence (AI) in English Language Teaching (ELT) can be seen as both a benefit and a potential threat, depending on how it is used and implemented. On the one hand, AI technology has the potential to make language learning more efficient and effective, by providing personalized feedback and practice exercises tailored to the different student’s needs and learning style. By conducting an in-depth analysis of the existing literature on this topic, the writers aim at gaining a deeper understanding of the ways in which AI is being used to enhance the learning of English as a foreign language. Moreover, the literature review has involved an extensive search, mostly, for relevant scholarly articles, books, and additional sources that explore the intersection of AI and ELT. Besides, this review has also resulted a deeper understanding of the benefits and threats of using AI in ELT.